2020
DOI: 10.1016/j.heliyon.2020.e05593
|View full text |Cite|
|
Sign up to set email alerts
|

The prevalence of general anxiety disorder and its associated factors among women attending the perinatal service of Dilla University referral hospital, Ethiopia during the COVID-19 pandemic

Abstract: Background: Coronavirus is rapidly increasing in Ethiopia, and the number of perinatal service users at the hospital decreased due to the fear of contracting the virus. The mental health of a pregnant mother is vital for preventing pregnancy and birth-related complications. This study aimed to determine the magnitude and associated factors of General anxiety disorder among perinatal service users in Dilla University referral hospital, Dilla, Ethiopia. Methods: A hospital-based cross-sectional study was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 26 publications
3
28
0
Order By: Relevance
“…Perceived low social support and social isolation were associated with increased psychological symptoms ( 57 , 61 , 62 , 65 , 78 , 96 , 109 , 115 , 120 , 129 ), and increased social support acted as a protective factor ( 71 , 96 ). In addition, general conflict, poor family functioning and martial distress emerged as significant risk factors for perinatal anxiety during the pandemic ( 56 , 72 , 74 , 81 , 89 , 98 , 116 , 117 , 128 ).…”
Section: Resultsmentioning
confidence: 99%
“…Perceived low social support and social isolation were associated with increased psychological symptoms ( 57 , 61 , 62 , 65 , 78 , 96 , 109 , 115 , 120 , 129 ), and increased social support acted as a protective factor ( 71 , 96 ). In addition, general conflict, poor family functioning and martial distress emerged as significant risk factors for perinatal anxiety during the pandemic ( 56 , 72 , 74 , 81 , 89 , 98 , 116 , 117 , 128 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, two recent studies in the Ethiopian population determined the prevalence and determinants of anxiety in healthcare workers ( 14 ) and women attending prenatal care ( 15 ). However, there are few reports which determined the prevalence of anxiety in the Ethiopian student population and studied its associated conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 21 reports estimated the prevalence of anxiety in pregnant women during this pandemic [ 29 , 30 , 31 , 32 , 33 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. Depression, Anxiety and Stress Scale-21 (DASS-21), the Edinburg Perinatal Depression Scale (EPDS), the Hospital Anxiety, Depression, Stress Scale (HADS), The Patient Health Questionnaire (PHQ-9), the General Anxiety Disorder-7 (GAD-7), the item 3 of the Oslo Social Support Scale (OSSS-3), the Self-Rating Anxiety Scale (SAS), the Trait Subscale of the Spielberg State-Trait anxiety Inventory (STAI-T), Beck Anxiety Inventory (BAI), the Inventory of Depression and Anxiety Symptoms II (IDAS-II), the Kessler Psychological Distress Scale (K10), the Mental Health Inventory—Short Form (MHI-5), the Patient-Reported Outcomes Measurement Information System (PROMIS), a modified version of the Pregnancy-related Anxiety Scale (PrAS), the Perceived Stress Scale (PSS), the Post-traumatic Stress Disorder Checklist 5 (PCL-5) and the Pandemic-related Pregnancy Stress Scale (PREPS) questionnaires were used to assess symptoms of anxiety, the majority self-report.…”
Section: Resultsmentioning
confidence: 99%
“…The main causes of anxiety reported in pregnant women during the pandemic were using a public transport (87.5%), COVID-19 infection of a family member (71.1%), being in public places (70%), concern for pregnancy complications and fetus health (70%), attending gynecological appointments (68.7%), becoming infected by COVID-19 (59.2%) and birth time (55.4%) [ 50 ]. The results reported from a cohort showed that most patients (82.5%) had concerns about infecting their babies during delivery [ 42 ].…”
Section: Resultsmentioning
confidence: 99%